Pflege-Report 2020 2020
DOI: 10.1007/978-3-662-61362-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Pflegebedürftigkeit in Deutschland

Abstract: Zusammenfassung Zusammenfassung Der Beitrag liefert ein ausführliches Bild zum Stand der Pflegebedürftigkeit und der gesundheitlichen Versorgung der Pflegebedürftigen in Deutschland. Die Analysen basieren auf GKV-standardisierten AOK-Daten. Sie zeigen Prävalenz, Verläufe und Versorgungsformen der Pflege sowie Kennzahlen zur gesundheitlichen Versorgung der Pflegebedürftigen. Im Fokus stehen die Inanspruchnahme von ärztlichen und stationären Leistungen, Polymedikation und Verordnungen von PRISCUS-Wirkstoffen un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
3
1
0
4
Order By: Relevance
“…The CG included 31 (79%) females and 8 (21%) males, who were aged from 61 to 102 (mean 86.66, SD 8.76) years. The distribution of age (mean 86.06, SD 8.2 years) and gender (female n=53, 76%, male n=17, 24%) in the total sample roughly corresponded to the findings on the need for care in Germany [ 65 ].…”
Section: Resultssupporting
confidence: 72%
“…The CG included 31 (79%) females and 8 (21%) males, who were aged from 61 to 102 (mean 86.66, SD 8.76) years. The distribution of age (mean 86.06, SD 8.2 years) and gender (female n=53, 76%, male n=17, 24%) in the total sample roughly corresponded to the findings on the need for care in Germany [ 65 ].…”
Section: Resultssupporting
confidence: 72%
“…The control group included 55 participants (41 females and 14 males) aged between 60 and 107 years (mean age 84.24 years, SD 9.33 years). The distributions of age (mean 83.03 years, SD 8.2 years) and gender (66 females, 71%; 28 males, 29%) of the total sample roughly corresponded to the current findings on the need for care in Germany [ 39 ].…”
Section: Methodssupporting
confidence: 77%
“…The baseline comparison showed that the intervention and control groups did not differ statistically in any variable at the beginning of the intervention and were therefore deemed comparable. The relevant sociodemographic variables roughly corresponded to the current findings about the need for long-term care in Germany [ 39 ].…”
Section: Discussionsupporting
confidence: 60%
“…Most nursing home residents suffer from multimorbidity, frailty, cognitive impairments, and polypharmacy, all of which necessitate access to and utilization of medical care [4][5][6][7]. In nursing homes, almost all residents have regular contact with general practitioners (GPs) [8][9][10][11][12]. However, only approximately half of all residents have contact with dentists at least once a year [8,10,11].…”
Section: Introductionmentioning
confidence: 99%